Capital intelectual: um estudo de caso numa empresa de jornalismo - de Holanda, Lucyanno Moreira Cardoso; Silva Filho, Joel Freire; da Rocha, Ricardo Campos (Revista Gestão da Produção Operações e Sistemas, 2007)
The major productivity factor in an informational society – as the current one – is the people’s and enterprise’scapacity to generate, process and transform information and knowledge into economic assets. In order to acquirepotentialized and continuous knowledge in the organizations, Karl Erik Sveiby emphasizes that it is necessaryto have three structures: internal, external and the employees’ competences, in addition to establishing coherentstrategies focused on the knowledge, not on information. Within this perspective, this paper aims at verifyingthe intangible assets of a journalism enterprise located at Campina Grande, Paraíba, Brazil, based on the modelproposed by Sveiby (1998). The study is characterized as exploratory, with the use of qualitative techniques todata collection and analysis. The obtained results point out to the fact that, in the studied enterprise, there is notcurrently any systematic policy implemented that is specifically focused on intangible assets.Keywords: Intellectual capital; Knowledge management; Intangible assets; Service production.